Análisis de sensibilidad de la prueba de Student para una muestra (2011)
Student’s t statistic is not a monotonic function of the diﬀerence between x and µ0, since it is modiﬁed by alterations in the data that also aﬀect the value of the variance. In this paper the property is used to analyze the stability of the test when the p-value is close to the signiﬁcance level.